Impact of personality on cadet academic and military performance within mediating role of self-efficacy - Bekesiene, Svajone (Frontiers in Psychology, 2023)
Pursuing an officer's education at military academies is very difficult not only physically but also psychologically. Cadets are required to be prepared to lead in extreme environments upon graduation. Despite the fact that military tasks are technically complex, the individual operational activities of soldiers are gaining more and more strategic meaning. Therefore, the importance of selecting the process and military education programmes for soldiers is increasingly stressed. Cognitive abilities and skills individually predict performance in academic and professional settings, but it is less clear how personality can influence performance. Therefore, this study focused on the explanation of the individual factors that affect the achievements of the cadets. Specifically, the objective of this study was to examine direct and mediated relationships between personality traits and the military and academic performance of cadets. Methods: This study followed a quantitative method analysis. The research models were assessed using the structural equation modelling technique. Bootstrap was applied to evaluate a 95% level confidence interval on estimates with 5000 bootstrap samples and to evaluate direct and indirect effects. The analysis was based on a sample of 120 cadets from the Lithuanian Military Academy. The effects on military and academic performance were evaluated using the Self-Efficacy scale, and the Big Five personality trait scale, academic performance was evaluated through academic grades, and military performance was evaluated using instructor ratings. Results: To support our hypotheses, it was found that self-efficacy has a mediating effect on the performance of cadets. Additionally, the traits of conscientiousness, openness to experience, and extraversion were related to both military and academic performance. Furthermore, self-efficacy appeared as a partial mediator of the relationship between personality traits and cadet performance. The findings of this study help clarify the relationship between the personality traits of the cadets and the military and academic performance. In addition, these results may be useful for the further development of military education and training, for the development of testing, and selection of military personnel.